The Influence of Motivation, Lifestyle, and Trust on Purchase Decisions at Marketplace Shopee - Hana Fahmilia; Hendri Hermawan Adinugraha (Al-'Aqdu: Journal of Islamic Economics Law, 2022)
The challenges faced in making sales transactions are the main trigger for this research, which is faced by the current rampant online buying and selling system, especially among students of the Islamic Economics and Business Faculty IAIN Pekalongan. The shopee marketplace is one of the trends where the products available are varied and the convenience provided when buying and selling at shopee. This study uses quantitative research methods with sampling technique using the slovin formula. Validity test, reliability test, normality test, classical assumption test, multiple linear regression test, T test and F test, and the coefficient of determination test were all used in the data collection stage. The results show that (1) In the Islamic economic perspective, motivation has a positive and significant impact on purchasing decisions in the Shopee marketplace (2) In the Islamic economic perspective, lifestyle has a positive and significant impact on purchasing decisions in the Shopee marketplace (3) In the perspective of the Islamic economy Islamic economics, trust has a positive and significant impact on purchasing decisions in the Shopee marketplace (4) In the perspective of Islamic economics, motivation, lifestyle, and trust have a positive and significant impact on purchasing decisions in the Shopee marketplace.